Correlation of distance walked in audio signal-modified shuttle walk test with six-minute walk test - Rishi Gopalakrishnan; Richa Hirendra Rai; Rupak Singla; Lokender Kumar; Nidhi Chandra Ponath Sivan (Monaldi Archives for Chest Disease)
The literature review suggested that the audio signal-modified shuttle walk test (SWTSR) was equally reliable and valid when compared to the conventional shuttle walk test. A comparison of SWTSR with the six-minute walk test (6MWT), which is considered the gold standard in walk tests, allowed us to evaluate the SWTSR and determine its validity and reliability as an alternative or supplement to the 6MWT. The objective of this study was to determine the correlation between the distances walked during a SWTSR and the 6MWT in healthy, normal adults. The study recruited 42 healthy normal adults who underwent 6MWT and SWTSR on the same day. The correlation was assessed by Pearson’s correlation coefficient, and agreement between the tests was assessed using a Bland-Altman plot. Additionally, the acceptability of the modified test in comparison to the 6MWT was assessed by the Likert scale. The distances walked (mean ± standard deviation) in the 6MWT and SWTSR were 693.8±58.3 and 951.4±139.7 m, respectively (Pearson’s correlation coefficient of 0.918). The distance covered by the study participants in the 6MWT and SWTSR showed a strong correlation with spirometry results. The SWTSR induced a greater physiological response compared to the 6MWT. The acceptability of the SWTSR was comparable to that of the 6MWT. The distance walked in the SWTSR shows a strong positive correlation with the 6MWT and has comparable acceptability with the 6MWT. The SWTSR may provide a better index of the patient’s ability for his activities of daily living and may be a better measure for studying exercise tolerance than the 6MWT in certain clinical settings.